POLYDIOXANONE VERSUS POLYPROPYLENE CLOSURE FOR MIDLINE ABDOMINAL INCISIONS - Naz, Samina; Memon, Sohail Ahmed; Jamali, Mansoor Ali; Ahmed, Muhammad Rashid; Almani, Tahmida (Journal of Ayub Medical College Abbottabad, 2017)
Background: Midline laparotomy is the most common technique of abdominal incisions because it is simple, provides adequate exposure to all four quadrants, and is rapid to open. A major problem after midline laparotomy remains the adequate technique of abdominal fascia closure. This study was conducted to see the role of Polydioxanone and Prolene for midline abdominal closure in terms of postoperative wound infection and wound pain. Methods: This study was carried out at surgical unit II, Federal Government Services Hospital Islamabad. Patients were equally divided in two groups, i.e., A and B. Groups A and B patients undergone midline abdominal closure with Polydioxanone number 1 and Polypropylene number 1 sutures respectively. Results: Total 620 patients were included in this study. Post-operative wound pain score according to Visual analogue scale (VAS) was compared in terms of no pain (0), mild pain (1-3), moderate pain (4-6), severe pain (7-9). In group A (Polydioxanone), the frequency and percentages of no, mild, moderate and severe pain were 101 (32.6%), 95 (30.6%), 81 (26.1%) and 33 (10.6%) respectively, where as in group B (polypropylene) it was 82 (26.5%), 43 (13.9%), 59 (19%) and 126 (40.6%) respectively. Similarly, the frequency and percentages of post-operative wound infection in group A (Polydioxanone) and group B (polypropylene) was 105 (33.9%) and 208 (67.1%) respectively. Conclusion: Polydioxanone results in less wound pain and wound infection when compared to Polypropylene. Keywords: Abdominal wound closure; Midline laparotomy; Wound pain; Wound infection